Volunteering and the State - Franz Hackl; Martin Halla; Gerald J. Pruckner (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
This paper explores the capability of the state to affect the individuals decision to work for free. For this purpose we combine individual-level data from the European and World Values Survey with macroeconomic and political variables for OECD member countries. Empirically we identify three channels for crowding out of voluntary labor. Firstly, an increase in public social expenditure decreases the probability that the individual will volunteer (fiscal crowding out). Secondly, a political consensus between individuals and the government also induces volunteers to reduce their unsalaried activities (consensual crowding out). And finally, the more a government supports democratization, the lower is the individuals engagement (participatory crowding out). Religiosity and a more unequal income distribution in a country increase individuals willingness to volunteer.
Keywords: H41; H44; H31; J22; I38; H11; D30; D64; 330; Volunteering; voluntary labor supply; private provision of public goods; public social expenditure; political consensus; democratization